Role of Maternal Serum Placental Protein 13 at 11-13 weeks of Pregnancy as a Predictor of Pre-eclampsia - Asma, Mahfuja; Sharmin, Farzana; Begum, Firoza; Begum, Mahbuba; Alam, Muhammad Mahmud (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Prediction of pre-eclampsia is very important during pregnancy. Objective: The purpose of the present study was to find out the role of maternal serum placental protein 13 at 11 to 13 weeks of pregnancy as a predictor of pre-eclampsia. Methodology: This prospective cohort study was carried out including 83 pregnant women with early gestation (11-13 weeks) attending the antenatal clinic of BSMMU hospital, Dhaka, during the period of July 2019 to December 2019 for a period of six months. Maternal serum was taken for measurement of Placental Protein 13 by ELISA technique. Then the subjects were regularly followed up to term. At each visit they were clinically evaluated by measuring blood pressure and testing urine for protein by heat coagulation method. Proteinuria was confirmed by measuring 24 hour urinary total protein. Result: Out of 83 cases, 5 developed preeclampsia. The mean value of Placental Protein 13 in non-preeclampsia patients was 167.5±8.79 and in pre-eclamptic patients was 131.54±20.06. The cutoff point value of Placental Protein 13 for prediction of preeclampsia was 0.68 MoM. Area under curve (AUC) was 0.93. Sensitivity, specificity, positive predictive value and negative predictive value of this test were 80.00%, 94.94%, 50.00% and 98.68% respectively. The accuracy of this test was 93.98%. Conclusion: In conclusion maternal serum Placental Protein 13 can predict risk of development of preeclampsia. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 47-51